Online learning in empowering mastery towards important events of the legend of Hang Tuah - Makmun, Rozaiman; Abu Bakar, Roslina; Taruna, Jariahtul Amal; Abdul Rahman, Sri Kartika (Human Resource Management Academic Research Society, 2022)
This action study is done to test the effectiveness of online learning in empowering student mastery towards important events of the Legend of Hang Tuah (LHT). This study is aimed to see the effect of using online learning in elevating the skill and understanding performance of students to master and dissect the important events of Hang Tuah Legend in the Malay Literature subect at the pre-university level in Brunei Darussalam. The objectives of this study are to identify the score min difference of student achievement in pre test and post test after following the online learning intervention using Kahoot and Google Classroom. Secondly, to summarize student perception towards their experience following learning using Kahoot and Google Classroom to master important events of the Legend of Hang Tuah. This study was carried out using the qualitative and quantitative approaches. Through the quantitative method, this study uses a first year pre-university class in a form six center in the Brunei and Muara district. The researcher applies online activity, based on Kahoot and Google Classroom to help students more in mastering the important events in LHT. This research was able to prove the effectiveness of online learning to enhance the mastery of students towards important event of Legend of Hang Tuah (LHT) through online learning, based on Kahoot and Google Classroom and to help student master more the LHT important event.